2019
DOI: 10.18388/abp.2019_2890
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells’ homing and cardiac tissue repair

Abstract: Nowadays, mesenchymal stem cells (MSCs) are essential players in cellular therapy and regenerative medicine. MSCs are used to treat cardiac disorders by intramyocardial injection or injection into the bloodstream. Therefore, a premise of successful MSC-based therapy is that the cells reach the site of injury and home the damaged tissue. In response to inflammatory conditions, MSCs can potentially move into the place of injury and colonize damaged tissues, where they participate in their regeneration. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…Many reports suggest that damaged tissue releases specific factors that act as chemoattractants to facilitate the adhesion, migration, and homing of MSCs in affected areas. Studies have shown that MSCs are capable of migrating to inflamed tissues in response to factors that are regulated under inflammation[ 4 , 58 , 59 ]. To date, many chemokines and growth factors have been identified that are involved in the migration process.…”
Section: Biochemical Factors Involved In the Migration Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports suggest that damaged tissue releases specific factors that act as chemoattractants to facilitate the adhesion, migration, and homing of MSCs in affected areas. Studies have shown that MSCs are capable of migrating to inflamed tissues in response to factors that are regulated under inflammation[ 4 , 58 , 59 ]. To date, many chemokines and growth factors have been identified that are involved in the migration process.…”
Section: Biochemical Factors Involved In the Migration Of Mscsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are a population of primary and non-specialized cells, which can be isolated from various tissues. Friedenstein et al [ 1 ] described a bone marrow-derived fibroblast-like cell for the first time, which later became the most extensively studied MSC and are sometimes regarded as the “gold standard.” Later, these cells were identified in nearly every tissue type (peripheral blood, adipose tissue, bone marrow, dental pulp)[ 1 - 4 ]. The human umbilical cord (UC), cord blood, placenta, and amniotic fluid have been shown to contain MSCs[ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…After sensing the injury signal released from damaged tissues, MSCs can be mobilized and migrate into injured tissues through peripheral circulation; this trafficking process is regulated by multiple mechanical factors (e.g., mechanical strain, shear stress, matrix stiffness, and microgravity) and chemical factors (including stromal derived factor-1/CXC chemokine receptor 4 axis, osteopontin, basic fibroblast growth factor, vascular endothelial growth factor-A, hepatocyte growth factor, insulin-like growth factor-1, platelet-derived growth factor, transforming growth factor-β1) 25 . Subsequently, MSCs reach the damaged tissue site and perform wound healing of damaged tissues in two key ways, i.e., paracrine (e.g., releasing bioactive factors: chemokines, cytokines, and growth factors) and/or directed differentiation to replace damaged cells (e.g., osteocytes, chondrocytes, cardiomyocytes, and endothelial cell differentiation) 26 . Over the recent decades of intensive studies, the bone morphogenic protein (BMP) signaling and wingless and int-1 (Wnt) signaling pathways have been demonstrated to regulate osteoblast and adipocyte differentiation of MSCs 27 .…”
Section: Therapeutic Potential Of Mscsmentioning
confidence: 99%
“…Previous studies of MSC transplantation in animal models and human patients have demonstrated improved therapeutic effects in terms of rapid wound healing and improved dermal regeneration [7,[28][29][30][31][32][33]. After systemic administration, MSCs are also capable of migrating to and engrafting in sites of inflammation where they exert local functional effects in the resident tissue [34][35][36][37][38]. In addition, MSCs regulate immune and inflammatory responses and can have a reparative effect through paracrine signaling by releasing biologically active molecules that affect cell migration, proliferation, gene expression, and survival of the surrounding cells [33,39].…”
Section: Introductionmentioning
confidence: 99%